Ketrampilan Berbahasa Inggris untuk Perawat Pada Program Studi Keperawatan Universitas Timor - Sefrina Maria Seuk (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Communication is part of nursing to patients. English is one of the communication tools in nursing. The geographical location of Belu Regency, which borders the State of Timor Leste, allows foreign patients to access services at the Belu Regency Hospital and Sito Husada Atambua Hospital. This is a challenge for nurses to prepare their English skills for nursing in order to provide better services to foreign patients. English proficiency for nursing is one of the indicators of the readiness of nurse human resources in border areas to welcome the golden era of Indonesia in 2045.